Pengembangan Media Permainan Susun Kata Berbasis Kelompok dalam Layanan Bimbingan Klasikal untuk Melatih Kerja Sama Siswa - Miftahul Jannah; Yenti Arsini (STIKes Ibnu Sina Ajibarang, 2026)
Students’ cooperation skills in elementary school need to be developed through structured and engaging guidance and counseling services. Initial findings at SD Al-Mukmin showed that third-grade students still experienced difficulties in group cooperation, such as unequal participation, dominant group members, ineffective communication, and dependence on more capable peers. This study aims to describe the needs analysis, development process, and feasibility and practicality levels of group-based word-arrangement game media to train students’ cooperation skills. This research used the Research and Development (R&D) method with the Four-D (4D) development model, limited to the Define, Design, and Develop stages. The research subjects consisted of one media expert validator, one material/guidance and counseling expert validator, one guidance and counseling teacher, and third-grade students of SD Al-Mukmin. The needs analysis and limited trial involved 24 third-grade students of SD Al-Mukmin. The media needs analysis obtained a score of 338 out of a maximum score of 384, with a percentage of 88.02%, categorized as highly needed. Meanwhile, the initial cooperation analysis obtained a score of 277 out of a maximum score of 480, with a percentage of 57.71%, indicating that students’ cooperation skills still needed to be developed. The feasibility test showed that the media expert validation obtained 100% and the material/guidance and counseling expert validation obtained 92.5%, both categorized as highly feasible. The practicality test showed that the teacher response obtained 100% and the student response obtained 96.09%, both categorized as highly practical. Thus, the group-based word-arrangement game media is feasible and practical to be used as guidance and counseling media to train elementary students’ cooperation skills.